Directed influence on anaerobic energy supply systems of qualified free style wrestlers - Sybil, M.G.; Pervachuk, R.V.; Chuiev, A.U. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to experimentally prove effectiveness of directed influence on anaerobic energy supply systems of free style wrestlers, considering individual characteristics of their bio energetic. Material: in this article the data of laboratory bicycle stress test «Vita maxima» and results of special control testing have been presented. 40 sportsmen participated in the experiment. Results: individual characteristics of dominating type of anaerobic energy supply have been determined. Statistically confident difference between development of lactate and a-lactate anaerobic energetic components were found. By the data of bio-chemical indicators’ changes the authors observed increase of adenosine triphosphate (glycolytic or creatine-phosphate) in some, weaker developed mechanisms of anaerobic re-synthesis. Ways of influence on anaerobic energy supply systems, considering individual characteristics of dominating of different components (lactate or a-lactate) have been found. Conclusions: it is recommended to take in consideration individual dominating type of energy supply.